(untitled) (Research, Society and Development, 2022)
Objective: The study aimed to analyze the epidemiological profile of individuals residing in the city of Rio de Janeiro who were affected by the Sars-CoV-2 virus infection with progression to Severe Acute Respiratory Syndrome (SARS). Methodology: This is an epidemiological, cross-sectional, descriptive study with a quantitative approach. Data were collected through public consultation on the website of the State of Rio de Janeiro, where the following variables were sought for analysis: sex, age group, number of hospital admissions, type of ventilatory support used, whether there was hospitalization in a intensive care, if there was evolution to death. Results: Of the residents of the city of Rio de Janeiro, it was found that 74.9% evolved to SARS as a result of COVID-19 infection, the most affected age group, 22.35%, were individuals between 60 and 69 years old, 93% required hospitalization, 48.9% required non-invasive ventilatory support, and 40.9% died. Conclusion: The study was able to draw a profile and showed that the hypothesis raised by the researchers is that the Sars-CoV-2 strain has a relevance to the previous strains in relation to the increase in SARS cases in the year 2020. Despite the collapse of many systems around the world, it was observed that the lack of knowledge to prepare clinical protocols that could really guide health professionals and also the lack of commitment of the current governments, mainly at the federal level, caused the establishment of chaos and even collaboration for not containing the spread of the virus.